Global prevalence of postoperative hypoxemia among adult and pediatric surgical patients: a systematic review and meta-analysis - Yosef Belay Bizuneh; Mulualem Endeshaw Zeleke; Ashebir Mamay Gebru; Destaw Fetene Teshome; Fantahun Ayenew Mekonnen; Dessie Abebaw Angaw; Amare Belete Getahun (BMC Anesthesiology)
Abstract Background Postoperative hypoxemia refers to a condition where oxygen levels in the tissues or blood drop to insufficient levels following surgery. The aim of this review is to determine the global prevalence of postoperative hypoxemia among adult and pediatric surgical patients through a systematic review and meta-analysis. Methods We performed a comprehensive search across multiple databases, including Pubmed, Embase and Scopus. Additionally, search engines such as Google Scholar and Google. The searching mechanism was using medical subject heading terms combining by Boolean operators. The process adhered to the PRISMA guidelines, ensuring a robust method for the review. The review was registered at PROSPERO with registration number CRD42024534623. Risk of bias or quality assessment was done using a standardized critical appraisal instrument. Publication bias was assessed using a funnel plot and Egger’s regression test. Pooled prevalence was estimated using random-effects. Subgroup analyses were conducted based on different factors. Additionally, to identify a single study effect sensitivity analysis was conducted. Result A total of 20 primary studies with 28,948 participants were included. The pooled prevalence of postoperative hypoxemia was 20.62% (95% CI: 17.02–24.22%). Publication bias was detected, with Egger’s regression test (p < 0.0001) indicating small-study effects. After imputing three studies, the pooled prevalence decreased from 20.62% (95% CI: 17.02–24.22%) to 16.76% (95% CI: 13.36–20.15%). Subgroup analysis showed the highest prevalence in Africa at 33.81% (95% CI: 25.51–42.1%) and in low-income countries at 33.81% (95% CI: 25.51–42.1%). Among emergency surgical patients, they had the higher prevalence, 21.38% (95% CI: 11.60-31.15%). Conclusion This meta-analysis showed a pooled prevalence of postoperative hypoxemia was 20.62%, which may be over reported due to publication bias. After data imputation, the revised prevalence was 16.76%. Higher rates are found in Africa and low-income countries, as well as emergency surgical patients.